High trait anxiety increases inferential false memories for negative (but not positive) emotional events. (March 2015) - Toffalini, Enrico; Mirandola, Chiara; Coli, Tatiana; Cornoldi, Cesare
Highlights: Anxious trait alone increases the occurrence of negative causal errors. Fewer negative than neutral causal errors occur in control participants. Anxious trait does not increase subjective confidence of causal errors. Abstract: Emotional disorders have been related with attentional and memory biases, especially for emotional material. Recent research has shown that depression, dysphoria and high internalizing traits are related with an increase of false memories for negative events. However, it is not clear whether anxiety alone may imply the same effect and whether it applies to all emotional events or only negative ones. The present study examined these questions by using a paradigm based on pictorial scripted material to analyze inferential memory errors for negative, positive and neutral everyday events in high-anxious vs. control young adults. Results showed an increase in negative (but not positive) inferential false memories in high-anxious individuals, even after controlling for depression level. On the contrary, negative material reduced false memories in control participants, further supporting previous research. It is concluded that high trait anxiety enhances elaboration of negative emotional material, which eventually leads to misremember causal antecedents of negative events as previously experienced while they were only inferred.